Recent Progress in Vaccine Development Against Chikungunya Virus - Gao, Shan; Song, Siqi; Zhang, Leiliang (Frontiers in Microbiology, 2019)
Chikungunya fever (CHIKF) is an acute infectious disease which is mediated by mosquito-transmitted chikungunya virus (CHIKV). People who infected with CHIKV could cause high fever, severe joint pain, skin rash and headache. In recent years, this disease has become one of the global public health problems. However, there is no licensed vaccine available to prevent CHIKV. Accumulating research data have provided novel approaches and new directions for the development of CHIKV vaccines. Our review focuses on the recent progress of CHIKV vaccines studies. The potential vaccine candidates are classified into seven types: inactivated vaccine, subunit vaccine, live-attenuated vaccine, recombinant virus-vectored vaccine, virus-like particle vaccine, chimeric vaccine and nucleic acid vaccine. These studies will shed important insights into future development of CHIKV vaccines.